STUDI KARAKTERISTIK GIZI UBI JALAR UNGU (Ipomoea batatas var Gunung Kawi) PADA BEBERAPA UMUR PANEN - Yaningsih, Herlin; Admadi, Bambang; Mulyani, Sri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 1 No 1 (2013): September, 2013)
This research aims to examine the nutritional characteristics of purple sweet potato couple harvesting date. This study used a Randomized Complete Design with treatment date purple sweet potato harvesting 110, 120, 130, and 140 days. The treatment is repeated four times so that the retrieved 16 units attempted. The variables observed in these study proximate levels on purple sweet potato. Based on observations of purple sweet potato harvesting age highly influence of moisture, ash, fat, protein, vitamin C, and carbohydrates. Based on the research result obtained, purple sweet potato on a 130-day harvesting date contain levels of proximate, i.e. contain a moisture content of 78,869 %, ash content of 0,010 %, fat content of 0,329 %, protein levels of 1,038 %, vitamin C levels of 0,145 mg/100 g, and carbohydrate levels of 19,611.
Keywords: 8